Sustitución de importaciones y cambio en el modelo tecnoproductivo en la Argentina peronista. Análisis sociotécnico del proyecto de producción automotriz local - Picabea, Facundo (2010)
During Juan Domingo Peron’s first presidency (1946-1952) an endogeneization of productive capacities was developed. In 1952, as a National Law, the government enacted the Second Quinquennial Plan, a program aimed at promoting heavy industrialization. Among the goals proposed the automotive industry was devised as a key element for the economic and social development. Through concepts such as technology resignification, problem-solving strategies, and socio-technical style, this article demonstrates how a series of heterogeneous elements (sector regulations, public capital, state propaganda, private companies, officers/executives, manual workers and users) were integrated in a co-building process, in which a series of device carriers of a society project were concurrently generated, and a society which employed them as tools for its transformation.